PENGARUH PEMBERIAN KOMPENSASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. GRAHA INFORMATIKA JAKARTA - Hanna Putri Ramadhanty; Tri Murwaningsih; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
The research aims at revealing whether: (1) The effect of giving compensation on job satisfaction at PT. Graha Informatika Jakarta; (2) The effect of work motivationi on job satisfaction at PT. Graha Informatika Jakarta; (3) Thei effect of giving compensation and work motivation simultaneously on job satisfaction at PT. Graha Informatika Jakarta.  This type of Quantitative descriptive research with descriptive survey method. Information presented in the study is the result of questioner that has been filled out by the employees of PT. Graha Informatika Jakarta. The research used purposive sampling technique, with a sample 68 respondents. The results showed that; (1) There is an effect of giving compensation on job satisfaction with the result of t test 3,174 > 1,973. (2) There is an effect of work motivation on job satisfaction with the result of t test 2,676 > 1,973. (3) There is an effect of giving compensation and work motivation simultaneously on job satisfaction with the result of F test 27,359 > 3,14.  The conclusion of the multiple linear regression analysis above show that 45% of job satisfaction is influenced by compensation and work motivation.